Identifying Candidate Genes that Underlie Cellular pH Sensitivity in Serotonin Neurons Using Transcriptomics: A Potential Role for Kir5.1 Channels - Puissant, Madeleine M.; Mouradian, Gary C.; Liu, Pengyuan; Hodges, Matthew R. (Frontiers in Cellular Neuroscience, 2017)
Ventilation is continuously adjusted by a neural network to maintain blood gases and pH. Acute CO2 and/or pH regulation requires neural feedback from brainstem cells that encode CO2/pH to modulate ventilation, including but not limited to brainstem serotonin (5-HT) neurons. Brainstem 5-HT neurons modulate ventilation and are stimulated by hypercapnic acidosis, the sensitivity of which increases with increasing postnatal age. The proper function of brainstem 5-HT neurons, particularly during post-natal development is critical given that multiple abnormalities in the 5-HT system have been identified in victims of Sudden Infant Death Syndrome (SIDS). Here, we tested the hypothesis that there are age-dependent increases in expression of pH-sensitive ion channels in brainstem 5-HT neurons, which may underlie their cellular CO2/pH sensitivity. Midline raphe neurons were acutely dissociated from neonatal and mature transgenic SSePet-eGFP rats (which have eGFP expression in all 5-HT neurons) and sorted with fluorescence-activated cell sorting (FACS) into 5-HT-enriched and non-5-HT cell pools for subsequent RNA extraction, cDNA library preparation and RNA sequencing. Overlapping differential expression analyses pointed to age-dependent shifts in multiple ion channels, including but not limited to the pH-sensitive potassium ion (K+) channel genes kcnj10 (Kir4.1), kcnj16 (Kir5.1), kcnk1 (TWIK-1), kcnk3 (TASK-1) and kcnk9 (TASK-3). Intracellular contents isolated from single adult eGFP+ 5-HT neurons confirmed gene expression of Kir4.1, Kir5.1 and other K+ channels, but also showed heterogeneity in the expression of multiple genes. 5-HT neuron-enriched cell pools from selected post-natal ages showed increases in Kir4.1, Kir5.1, and TWIK-1, fitting with age-dependent increases in Kir4.1 and Kir5.1 protein expression in raphe tissue samples. Immunofluorescence imaging confirmed Kir5.1 protein was co-localized to brainstem neurons and glia including 5-HT neurons as expected. However, Kir4.1 protein expression was restricted to glia, suggesting that it may not contribute to 5-HT neuron pH sensitivity. Although there are caveats to this approach, the data suggest that pH-sensitive Kir5.1 channels may underlie cellular CO2/pH chemosensitivity in brainstem 5-HT neurons.